Save the Economy, Liberty, and Yourself: Christian Nationalism and Americans' Views on Government COVID-19 Restrictions. (29th December 2020) - Perry, Samuel L; Whitehead, Andrew L; Grubbs, Joshua B
Abstract: During the COVID-19 pandemic, state and local governments implemented lockdown restrictions that were tremendously polarizing. Those on the cultural and political left supported restrictions hoping to protect the vulnerable, while those on the cultural and political right challenged restrictions citing threats to the economy and liberty. We theorize that libertarian and authoritarian impulses within Christian nationalism undergirded much of the resistance to government restrictions. Analyzing national panel data collected before and during the pandemic, we find Christian nationalism is either the first or second strongest predictor that Americans prioritize the economy and liberty and deprioritize the vulnerable when asked about government restrictions. Religiosity works in the opposite direction, however. Findings underscore the centrality of Christian nationalism as an ideological driver of far-right discourse shaping COVID-19 responses.